2014
DOI: 10.4236/jgis.2014.64033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Land Cover Change Using Remotely Sensed Imagery and GIS: A Case Study of Omo-Shasha-Oluwa Forest Reserve, SW Nigeria (1986-2002)

Abstract: Spatial patterns of land cover changes in the Omo-Shasha-Oluwa Forest Reserves were conducted on Landsat TM and ETM+ imageries of 1986 and 2002 using remote sensing and GIS techniques. Extent of tree plantation (Gmelina arborea) grew from about 145 sq. km in 1986 to about 322 sq. km in 2002 (122% increase). The natural forest declined from about 2569 sq. km in 1986 to about 2253 sq. km by 2002, while the non-forest areas increased by some 5% from 341 km 2 in 1986 to about 490 km 2 by 2002. Land cover pattern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The study by Adedeji and Adeofun, (2014) in the Omo-Shasha-Oluwa Forest Reserves showed that between 1986 and 2002, natural forest habitats decreased by 10% while plantations and non-forest areas increased by 6% and 5% respectively. This rate of loss of natural forests need to be curbed as the condition of natural habitats is important for biodiversity and degraded or fragmented habitats are less likely to be able to support their full complement of species (Aichi Biodiversity Target 5) especially a wide-ranging keystone species like the forest elephant.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Adedeji and Adeofun, (2014) in the Omo-Shasha-Oluwa Forest Reserves showed that between 1986 and 2002, natural forest habitats decreased by 10% while plantations and non-forest areas increased by 6% and 5% respectively. This rate of loss of natural forests need to be curbed as the condition of natural habitats is important for biodiversity and degraded or fragmented habitats are less likely to be able to support their full complement of species (Aichi Biodiversity Target 5) especially a wide-ranging keystone species like the forest elephant.…”
Section: Discussionmentioning
confidence: 99%
“…Omo Forest Reserve (OFR) is 1325 km 2 , Shasha Forest Reserve (SFR) covers about 310km 2 , while Oluwa Forest Reserve (OlFR) covers about 827 km 2 . Rainfall and temperature within the reserves averaged 2050 mm and 27˚C respectively (Adedeji and Adeofun, 2014).…”
Section: Study Areasmentioning
confidence: 99%
“…Vegetatively, the study area is a lowland tropical rainforest that has been degraded to secondary forests, thickets, and farmlands of annual and perennial crops, with the exception of some parts of the Forest Reserves (Adedeji and Adeofun, 2014). Apart from the Strict Nature Reserve (SNR) situated at the north-western part of OFR, the forest is largely converted to mono plantations, mainly Gmelina arborea (Okoli and Ola-Adams, 1987).…”
Section: Study Areasmentioning
confidence: 99%
“…The species is distributed in 7 subpopulations, 2 of which are located in protected areas: the Omo-Oluwa-Shasha Forest Reserve located in Ondo State in Nigeria and the Korup National Park in Cameroon and Cross River National Park in Nigeria, which are in fact contiguous. Habitat loss outside the protected areas is a serious threat for C. capitatum , but loss of forest is also documented for the Omo-Oluwa-Shasha Forest Reserve and the Cross River National Park in Nigeria (Ite 1997; Adedeji and Adeofun 2014). …”
Section: Taxonomic Treatmentmentioning
confidence: 99%